2016
DOI: 10.3109/13561820.2015.1072803
|View full text |Cite
|
Sign up to set email alerts
|

A sociological exploration of the tensions related to interprofessional collaboration in acute-care discharge planning

Abstract: Patient discharge is a key concern in hospitals, particularly in acute care given the multifaceted and challenging nature of patients' health care needs. Policies on discharge have identified the importance of interprofessional collaboration, yet research has described its limitations in this clinical context. This study aimed to extend our understanding of interprofessional interactions related to discharge in a general internal medicine setting by using sociological theories to illuminate the existence of, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
1
33
0
2
Order By: Relevance
“…In relation to the wider literature, in a survey of over 600 clinical teams (Dixon-Woods et al, 2014) it was found that in addition to effort and skills of team members and good processes, organizational resources made available to teams including adequate staffing levels, were critical to their success. Top-down targets such as those related to admission and discharge, can result in healthcare providers focusing on throughput rather than interprofessional collaboration and quality of care (Allard & Bleakley, 2016;Goldman et al, 2016). Given the resource pressures in healthcare systems, it is important to be conscious of both the messages of interprofessional collaboration targeted at the individual level and the organizational resources being invested to enables these ideals.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the wider literature, in a survey of over 600 clinical teams (Dixon-Woods et al, 2014) it was found that in addition to effort and skills of team members and good processes, organizational resources made available to teams including adequate staffing levels, were critical to their success. Top-down targets such as those related to admission and discharge, can result in healthcare providers focusing on throughput rather than interprofessional collaboration and quality of care (Allard & Bleakley, 2016;Goldman et al, 2016). Given the resource pressures in healthcare systems, it is important to be conscious of both the messages of interprofessional collaboration targeted at the individual level and the organizational resources being invested to enables these ideals.…”
Section: Discussionmentioning
confidence: 99%
“…The role of occupational therapists (amongst others) is connected with their professional power which involves working within the interests of their employers, such as state or corporate healthcare systems which, as dominant players in the organisation of services, are able to determine how needs are met. Examples of this may be working within the need for corporate safety and limited liability in clinical decision making (Durocher, Gibson, & Rappolt, 2016), or organisational communication and efficiency priorities (Goldman et al 2016). These principles become margins within which people with disabilities and people with experiences of mental distress may be contained by groups of professional workers such as occupational therapists.…”
Section: Therapy and Justicementioning
confidence: 99%
“…This approach is affecting the range of professional groups in GIM, and healthcare more broadly, as they defend or adapt their professional boundaries and roles to these demands (Correia, 2013;Harvey, Thompson, Pearson, Willis, & Toffoli, 2017;Henderson, Willis, Toffoli, Hamilton, & Blackman, 2016;Newman & Lawler, 2009;Reeves, Nelson, & Zwarenstein, 2008;Shannon & French, 2005). For example, social workers, pharmacists, occupational therapists and physiotherapists in GIM units have experienced changes in their roles in the healthcare division of labour with greater emphasis on discharge-related responsibilities (Galati, Wong, Morra, & Wu, 2011;Goldman et al, 2016;Neeman et al, 2017). Physicians in these settings have pressures to prioritize their decision-making around patient flow with an increasing emphasis on the value of teaching residents about safe discharge (Greysen, Schiliro, Horwitz, Curry, & Bradley, 2012;Schoenborn & Christmas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…New discharge professional roles have been created to facilitate admissions and discharge in acute care medical units (Okoniewska et al, 2015). Nurses in managerial roles across a range of hospitals units have engaged in 'organizing work' that entails sophisticated technical, organizational and social skills (Allen, 2014); this has also been reported in the GIM context (Goldman et al, 2016). Challenging questions remain about the professional role of the nurse bedside carer in current healthcare systems (Allen, 2014(Allen, , 2015Heartfield, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation